Is Melatonin, Leptin or Their Combination More Effective on Oxidative Stress and Folliculogenesis in the Obese Rats - Tümentemur, G.; Altunkaynak, B.Z.; Kaplan, S. (Taylor and Francis Ltd, 2020)
In this study, we evaluated the effects of melatonin (Mel), leptin (Lep) or melatonin and leptin treatment on ovaries in control and obese rats. The animals were divided into control (NC), melatonin (NM), leptin (NL), melatonin–leptin (NML), obese (OC), obese–melatonin (OM), obese–leptin (OL), obese–melatonin–leptin (OML) groups. Body weights, peri-ovarian fat pads, volumetric parameters and numerical values of follicles were estimated. Also, the LH receptor (LHr) immune-positivity, catalase (CAT) and the myeloperoxidase (MPO) levels were determined. The body weight and peri-ovarian fat pads were significantly decreased following Mel (p <.05) treatment and, especially, Lep (p <.01) treatment. But, the ovarian weights were significantly increased following Lep (p <.05) and Mel (p <.01) treatment, in particular. The ovarian and cortex volume decreased in the OC group, and the cortex volume of the OC group was significantly higher than the Ob + Mel, Ob + Lep and Ob + Mel + Lep groups (p <.01). Besides, the volume of the cortex in the NL group was significantly higher than in the other groups (except for the NC group) (p <.01). Although, the total numbers of primordial and primary follicles in NC group were significantly higher than in the OC group (p <.001), the number of the primordial and primary follicles in OC group was significantly higher than in the OL (p <.05), OM (p <.05) and, especially, the OML groups (p <.001). Likewise, the number of the secondary follicles in the OML group was significantly less than that in the OC group (p <.05). The CAT and MPO activity of the OC group was significantly higher than in the NC group (p <.05) and also granulosa cell apoptosis had increased in obese rats; but it was decreased after Lep and Mel treatment. Otherwise, Lep and, in particular, Mel increased LHr positivity. We concluded that obesity could trigger abnormal ovarian function and polycystic ovary via inducing LHr apoptosis and suppressing ovarian folliculogenesis. Also, melatonin could be better for inhibition of apoptosis and modulation of folliculogenesis than leptin. These observations suggest that melatonin may act to reduce fertility in obese patients.Impact statementWhat is already known on this subject? Hormonal changes during reproductive cycle in obese women are particularly studied and there is not any study that evaluates the effects of melatonin and leptin, together. Whatthe results of this study add? The study has shown that obese rats have increased granulosa cell apoptosis and MPO activities but melatonin and leptin reduces the apoptosis and inflammation. Moreover, the obesity decreased, but melatonin and leptin increased LHR immunoreactivity in both the granulosa and theca cells. Whatthe implicationsareof these findings for clinical practice and/or further research? The results suggest that leptin and melatonin could decrease excess body weight in obese persons. Also, these hormones modulate the ovarian turn-over by regulating developing follicles. Therefore, leptin and especially melatonin could be used as a supplement to ovulation therapy. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Body Mass Index; Leptin; Melatonin; Ovarian Morphology; Stereology; Weight Loss